The behavior of NiO/GO nanoelectroseramics in different solvents: Synthesis, structural, thermal and electro-optical properties - Aydin, Cihat; Yildiz, Oktay Emre (Korean Assoc Crystal Growth, Inc, 2024)
The need for effective energy storage and clean energy alternatives is one of the greatest concerns in the modern world. The need can be met by the application of energy storage devices such as supercapacitors, batteries, fuel cells and other energy storage devices. Supercapacitors are devices dedicated to energy storage. In this study, graphene oxide/NiO nanoelectroseramics were synthesized using acetone, ethyl alcohol, 2-Methoxyethanol and pure water. NiO nanoparticles, which are the components of nanocomposites, were synthesized using the sol-gel method, and graphene oxide (GO) was synthesized using the Hummers method. XRD, SEM, FT-IR, DTA-TG, UV-vis analyzes were applied to the samples obtained. Nanosupercapacitive properties of metal oxide and graphene oxide doped nanocomposites obtained using different solvents were investigated. Electrochemical measurements of the produced nanoelectroseramics were carried out by cyclic voltammetry (CV), and the capacitance curves and impedance spectrometers of the electrodes were determined.
Keywords: Nanoelectroseramics; Supercapacitor; Metal oxide; Sol-gel; Hummers method